Case Report: Liraglutide for Weight Management in Beckwith-Wiedemann Syndromic Obesity - Caputo, Marina; Daffara, Tommaso; Bellone, Simonetta; Mancioppi, Valentina; Marzullo, Paolo; Aimaretti, Gianluca; Prodam, Flavia (Frontiers in Endocrinology, 2021)
Genetic obesity, including syndromic and non-syndromic forms, represents a minority of cases compared to essential obesity but gene dysregulations lead to complex clinical conditions that make their management particularly difficult. Among them, Beckwith–Wiedemann syndrome (BWS) is a multisystem human genomic imprinting disorder characterized by overgrowth. We describe the first case of liraglutide treatment in an 18-year-old boy patient affected by BWS complicated by macroglossia, cryptorchidism, nephroblastoma, organomegaly, microscopic lymphocytic colitis, pharmacologically treated arterial hypertension, obesity, and obstructive sleep apnea syndrome. He presented a normal cognitive development. Body mass index at the time of first transition visit in the adult endocrinology department at the age of 18-years-old was 40.6 kg/m2 without glucose metabolism impairment. Lifestyle interventions failed because of poor compliance. During 20 months of 3.0 mg liraglutide treatment, a weight loss of 19 kg (-13.3%) and BMI reduction of 6.8 points were registered without side effects. To date, liraglutide treatment was effective on obesity in 7 subjects with Prader Willy Syndrome and 14 with melanocortin-4 receptor mutations. The efficacy of liraglutide in BWS could be related to a crosstalk among glucagon-like peptide (GLP)-1 system, mechanisms related to the cyclin-dependent kinase inhibitor 1C (CDKN1C), and dopamine mesolimbic circuit. Clinical trials aiming at a tailored medicine in genetic obesity are needed.